Can Improved Biomass Cookstoves Contribute to REDD+ in Low-Income Countries? : Evidence from a Controlled Cooking Test Trial with Randomized Behavioral Treatments - Beyene, Abebe D.; Bluffstone, Randall; Dissanayake, Sahan; Gebreegziabher, Zenebe; Martinsson, Peter; Mekonnen, Alemu; Toman, Michael (World Bank, Washington, DC, 2015)
This paper provides field experiment–based evidence on the potential additional forest carbon sequestration that cleaner and more fuel-efficient cookstoves might generate. The paper focuses on the Mirt (meaning “best”) cookstove, which is used to bake injera, the staple food in Ethiopia. The analysis finds that the technology generates per-meal fuel savings of 22 to 31 percent compared with a traditional three-stone stove with little or no increase in cooking time. Because approximately 88 percent of harvests from Ethiopian forests are unsustainable, these findings suggest that the Mirt stove, and potentially improved cookstoves more generally, can contribute to reduced forest degradation. These savings may be creditable under the United Nations Collaborative Program on Reducing Emissions from Deforestation and Forest Degradation in Developing Countries. Because of the highly specific nature of the Mirt stove and the lack of refrigeration in rural Ethiopia, rebound effects are unlikely, but this analysis was unable completely to rule out such leakage. The conclusions are therefore indicative, pending evidence on the frequency of Mirt stove use in the field. The effects of six randomized behavioral treatments on fuelwood and cooking time outcomes were also evaluated, but limited effects were found.